Qur’an on Embryology: A Study of Qur’anic and Modern concept of Human Development - Mohammad, Ali (Universitas Islam Negeri Alauddin Makassar, 2020)
The present era is the most astonishing from a developmental point of view. People across the globe are impressed by the latest developments and, more particularly, by genetic engineering. From the academic point of view, debates are organized on religion and science. Intellectuals are trying to prove their stands in their respective fields. Religious scholars put their efforts to establish their stand as the most applicable in the present era. A good number of modern scholars like Keith Moore, Maurice Bucaille, etc. also supported some religious facts mentioned in religious books, mainly in the Quran related to embryology. Among the most debate table issues is the concept of human development in the Quran and gave rise to a comparative study between religion and science again. In this manuscript, an analytical approach is applied to find the compatibility of Qur’anic embryology and modern embryology to pinnacle and galvanize Qur’anic modern attitude.